Development and implementation of a significantly low-cost 3D bioprinter using recycled scrap material - Gomes Gama, Jaciara Fernanda; Dias, Evellyn Araujo; Aguiar Coelho, Rosângela Marques Gonçalves; Chagas, André Maia; Aguiar Coelho Nt, José; Alves, Luiz Anastacio (Frontiers in Bioengineering and Biotechnology, 2023)
The field of 3D bioengineering proposes to effectively contribute to the manufacture of artificial multicellular organ/tissues and the understanding of complex cellular mechanisms. In this regard, 3D cell cultures comprise a promising bioengineering possibility for the alternative treatment of organ function loss, potentially improving patient life expectancies. Patients with end-stage disease, for example, could benefit from treatment until organ transplantation or even undergo organ function restoration. Currently, 3D bioprinters can produce tissues such as trachea cartilage or artificial skin. Most low-cost 3D bioprinters are built from fused deposition modeling 3D printer frames modified for the deposition of biologically compatible material, ranging between $13.000,00 and $300.000,00. Furthermore, the cost of consumables should also be considered as they, can range from $3,85 and $100.000,00 per gram, making biomaterials expensive, hindering bioprinting access. In this context, our report describes the first prototype of a significantly low-cost 3D bioprinter built from recycled scrap metal and off-the-shelf electronics. We demonstrate the functionalized process and methodology proof of concept and aim to test it in different biological tissue scaffolds in the future, using affordable materials and open-source methodologies, thus democratizing the state of the art of this technology.